The FTO variant is associated with chronic complications of diabetes mellitus in Czech population - Hubacek, Jaroslav A; Dlouha, Dana; Klementova, Marta; Lanska, Vera; Neskudla, Tomas; Pelikanova, Terezie (Gene, 2018)
BACKGROUND: Genome-wide association studies have resulted in the identification of the FTO gene as an important genetic determinant of diabetes mellitus. The aim of this study was to confirm the role of this gene in the development of DM in the Czech-Slavonic population and to analyse whether this gene is associated with common DM complications. METHODS: Two groups of patients (814 with T1DM and 848 with T2DM) and a group of healthy controls (2339 individuals) - both of Czech origin - were genotyped for the FTO rs17817449 SNP. ANOVA and logistic regression were used for the statistical evaluations. RESULTS: The frequency of the GG genotype was significantly higher in T2DM (25.4% vs. 16.7%, P<0.0005) but not in T1DM patients (19.3% vs. 16.7%, P=0.20) than in controls. The increased risk of development of diabetic nephropathy was observed both for T1DM patients (GG vs. TT homozygotes, P<0.01) and T2DM patients (G carriers vs. TT homozygotes, P<0.05). FTO genotype predicted the development of diabetic neuropathy (GG vs. TT comparison; P<0.01) in the T2DM patients only. No association between FTO genotype and development of retinopathy was detected. All presented values are after adjustment for age, sex, BMI and duration of diabetes. CONCLUSIONS: We confirm the association between the FTO rs17817449 SNP and susceptibility to T2DM in the Czech-Slavonic population. The same variant is associated with a spectrum of chronic complications in both types of diabetes.
Keywords: Diabetic Neuropathies; logistické modely; Polymorphism, Single Nucleotide; Humans; Chronic complications; diabetická retinopatie; genetické asociační studie; lidé středního věku; FTO; jednonukleotidový polymorfismus; Female; Aged; mladý dospělý; dospělí; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; senioři; lidé; Genotype; BMI; Diabetes Mellitus, Type 2; diabetes mellitus 1. typu; Adult; ženské pohlaví; diabetické nefropatie; Genetic Association Studies; Male; Middle Aged; Genetic Predisposition to Disease; genetická predispozice k nemoci; Czech Republic; Diabetic Retinopathy; Aged, 80 and over; Diabetic Nephropathies; Young Adult; senioři nad 80 let; genotyp; gen pro FTO; Česká republika; mužské pohlaví; Diabetes mellitus; diabetes mellitus 2. typu; Logistic Models; diabetické neuropatie; Diabetes Mellitus, Type 1; SNP